PENGARUH GROWTH OPPORTUNITY DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Murdiansyah "; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to test partially and simultaneously the effect of growth opportunity and firm size on firm value. Where the independent variables in this study are growth opportunity and company size while the dependent variable is the value of the company. The sample used is secondary data derived from the financial statements of pulp and paper companies listed on the Indonesia Stock Exchange from 2011 to 2015.This study uses secondary data from the company's financial statements. Sampling uses purposive sampling method. Data analysis using simple and multiple linear regression analysis, test coefficient of determination, t test and F test with SPSS 20.The results of this study indicate that the growth opportunity variable does not affect the firm value and the variable size of the company does not affect the firm value of pulp and paper companies listed on the Indonesia Stock Exchange. The simultaneous test results (F test) show no influence of growth opportunity and firm size variables on firm value in pulp and paper companies listed on the Indonesia Stock Exchange.Keywords: Growth Opportunity, Company Size, Company Value